FIGHTING COCACOLANISATION IN PLACHIMADA : Water, soft drinks and a tragedy of the commons in an Indian village - Eva Wramner (2004)
Plachimada is a small village in the South Indian state of Kerala suffering from severe water shortage since the global soft drink manufacturer Coca-Cola started their operations there four years ago. The factory is located in a rural residential area several miles from the nearest town. Groundwater is a common pool resource vital to us all but especially important to a poor agricultural community consisting primarily of indigenous people. The thesis puts Garrett Hardin's theory of privatisation as a solution to The Tragedy of the Commons to a test by setting his views up against the ideas of Vandana Shiva who instead advocates local community control. The villagers of Plachimada have been protesting against the Coca-Cola unit for more than two years. A continuos dharna or sit-down strike is held every day and night opposite the factory gates. The local government, the Perumatty panchayat, is fighting for the closure of the plant in courtrooms and government buildings and have so far obtained a temporary shut down of the bottling unit. This conflict is also about the panchayat's constitutional right to self-govern. The decentralisation process in Kerala seem to be losing its momentum; the state government is promoting industrialisation in the name of development.